2000
DOI: 10.1046/j.1469-7580.2000.19720221.x
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations in the human paranasal sinus region studied by CT

Abstract: A precise knowledge of the anatomy of the paranasal sinuses is essential for the clinician. Conventional radiology does not permit a detailed study of the nasal cavity and paranasal sinuses, and has now largely been replaced by computerised tomographic (CT) imaging. This gives an applied anatomical view of the region and the anatomical variants that are very often found. The detection of these variants to prevent potential hazards is essential for the use of current of endoscopic surgery on the sinuses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
76
4
8

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 14 publications
13
76
4
8
Order By: Relevance
“…Similar finding were observed by Perez et al (1) who reported the prevalence of deviated nasal septum to be about 80%. Dua et al (2) and Asruddin et al (3) found prevalence of 44% and 38% of deviated nasal septum in their respective studies.…”
Section: Figure 4 Nasal Septal Deviationsupporting
confidence: 79%
“…Similar finding were observed by Perez et al (1) who reported the prevalence of deviated nasal septum to be about 80%. Dua et al (2) and Asruddin et al (3) found prevalence of 44% and 38% of deviated nasal septum in their respective studies.…”
Section: Figure 4 Nasal Septal Deviationsupporting
confidence: 79%
“…Severino Aires de Araujo Neto et al, reported relatively less anatomical variations 65% in the osteomeatal complex of the chronic rhino sinusitis cases [13]. Perez et al, also observed similar prevalence of anatomical variations in the chronic sinusitis cases [14].…”
Section: Discussionmentioning
confidence: 93%
“…[Table/ Fig-1]: Showing the Osteomeatal complex (OMC)-(a) The OMC-small compartment located in the region between the middle turbinate and the lateral nasal wall in the middle meatus-represents the key region for the drainage for the maxillary, anterior ethmoid and frontal sinuses in chronic rhino sinusitis cases [14,24]. The prevalence of concha bullosa in our study is on the higher side when compared to the findings of Stallmann et al, [20], Maru et al, [25] and Alkire BC et al, [26] who reported it to be 44%, 42.6% and 41.7% respectively.…”
Section: Concha Bullosamentioning
confidence: 99%
“…5,14 This enormous variability in the frequency of The variability in the prevalence of Haller cells could also be explained on the basis of the patients' age group and race, and on the CT techniques used. 16 In the present study, we generated our own criteria of definition; the major criterion was based primarily on the distinction between Haller cells and infraorbital recess of maxillary sinus.…”
Section: Discussionmentioning
confidence: 99%